The unaccountable Federal Accountability Act: Goodbye to responsible government? - Sutherland, S. L. (Revue Gouvernance / Governance Review, 2006)
The article argues that the Federal Accountability Act or, as of November, 2006, C-2, is an unaccountable piece of legislation in the sense that it is not explicable or intelligible. Second, to take the risk of imposing so many unrelated measures on federal institutions at one time is not a responsible action. There is an unevaluated risk of destabilizing the institutions of government and the public service. Certainly some provisions of the bill, such as the creation of a parliamentary budget office as an executive agency, and the creation of a federal director of public prosecutions, might well merit study as selfstanding measures. But most other provisions, on examination, threaten to destabilize or end responsible government in Canada. The paper argues that several measures clearly fall into this latter category. Among these are measures to provide for heavy regulation and summary punishment of both parliamentarians and senior public servants, as well as for the “naming and blaming and shaming” of senior public servants at the cost of introducing a policy-administration dichotomy, plus the excessive grants of powers to agents or officers of Parliament and the creation of new “parliamentary” bureaucracies that in fact perform executive functions. The manner of passing the bill in the House was also of doubtful fairness, given that the New Democratic Party joined in a partnership with the government to rush the bill through the Legislative Committee of the House of Commons.